2019
DOI: 10.4067/s0718-18762019000300109
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Students' Hedonic Motivation System Model to Gamified Learning Environment

Abstract: The acceptance of gamified learning environment is rapidly becoming inevitable in educational learning environment. This gives a widespread popularity by deploying Gamification in to present day curriculum as part of a new educational technology tool. This study addresses perception and usage of gamified learning environment from hedonic motivation perspective through incorporating the Hedonic-Motivation System Adoption Model to Gamified Learning Environment. In this study, a model was developed and tested usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
56
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 28 publications
12
56
0
4
Order By: Relevance
“…Grounded in flow-based cognitive absorption (CA), Lowry et al (2012) improved the HMS by integrating intrinsic motivations, such as curiosity and joy in the HMSAM. Oluwajana et al (2019) found that curiosity, joy, and perceived usefulness have a direct impact on behavior intention based on HMSAM. Past studies also provided empirical evidence linkages between behavioral intention intrinsic motivations (i.e., curiosity, joy, and perceived usefulness) (e.g., Koo and Choi, 2010;Shu, 2014;Mohammadi, 2015).…”
Section: Hedonic-motivation System Adoption Modelmentioning
confidence: 90%
“…Grounded in flow-based cognitive absorption (CA), Lowry et al (2012) improved the HMS by integrating intrinsic motivations, such as curiosity and joy in the HMSAM. Oluwajana et al (2019) found that curiosity, joy, and perceived usefulness have a direct impact on behavior intention based on HMSAM. Past studies also provided empirical evidence linkages between behavioral intention intrinsic motivations (i.e., curiosity, joy, and perceived usefulness) (e.g., Koo and Choi, 2010;Shu, 2014;Mohammadi, 2015).…”
Section: Hedonic-motivation System Adoption Modelmentioning
confidence: 90%
“…Therefore, mbanking attractiveness makes consumers habitual towards gamification. A study addressed the perception and usage of the gamified learning environment from a hedonic motivation perspective and found enjoyment is significant with BI (Oluwajana, Idowu, Nat, Vanduhe, & Fadiya, 2019). On the other hand, gamification provides fun and pleasure to use technology, hence the study tried to investigate how HM affects gamification.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…CA is defined as a state of deep involvement and is an individual's holistic experience when interacting with technology such as a website [38]. Cognitive absorption was proposed as one of the factors determining the continuance usage of electronic services [32,39]. Conceivably, CA is likely to be a driving force behind consumers' completion of an online transaction.…”
Section: Cognitive Absorptionmentioning
confidence: 99%